Death knell or revival?: Navigating religious education in the age of the non-religious - Wareham, Ruth J. (Journal of Religious Education, 2023)
England and Wales are now amongst the least religious countries in the world. According to Census data between 2011 and 2021, the number of people identifying as having "No Religion" jumped by over 8 million, from 25% to 37%. Further, although there was a small upward shift in those identifying with minority religions, during the same period, the number of people identifying as Christian dropped by 5.5 million to 46.2% of the population. Wales is particularly irreligious. Here, 47% ticked "No Religion" compared to 44% "Christian". But even in Northern Ireland, where the majority still identify with a Christian denomination, the non-religious population has nearly doubled (from 10 to 17%) in the last decade. This surge in the non-religious will (and ought to) affect policy in a wide range of areas, but it is likely to be most profoundly felt in education; be that via reforms designed to better accommodate non-religious learners or attempts to reverse what is seen as a threatening trend by some religious groups and organisations. In this paper I explore the implications of this rapid demographic shift on religious education (RE). I argue that, while some may view the growth of the non-religious as a "death knell" signalling the subject's impending demise, it actually presents an unparalleled opportunity for revitalisation.